Correlation of Self-Management Behavior with Blood Pressure in Productive Age Hypertension Patients : Cross-Sectional Study at UPT Puskesmas Mentikan Mojokerto City - Evitasari, Rika Putri; Yuniarti, Enny Virda; Merbawani , Raras (Kirana Publisher (KNPub), 2025)
Hypertension is known as the